Evaluation of Content of Physiotherapy Care Given by Stroke Informal Caregivers (African Journal of Biomedical Research, 2023)
Informal caregivers taking charge of the continued care. Provision of adequate information, the need for skills in the aspect of home care and aspect in the management of stroke survivors can help create environment where health-care providers and informal caregivers partners in holistic stroke care and rehabilitation towards recovery of stroke survivors and minimise the risk of further injuries. However, there is need to assess the level of involvement of caregivers in home care programme. This study therefore sought to evaluate the content of physiotherapy care given by stroke informal caregivers. This cross-sectional analytic study was conducted among stroke informal caregivers in three secondary and tertiary hospitals in Lagos State. Sample size was 70. The participants were selected using consecutive sampling technique. Data was collected using structured questionnaire that was self-administered to the informal caregivers. Data analysis was carried out using SPSS Version 20 software and summarised using descriptive statistics. This study revealed that 61.4% of the informal caregivers knew the brain was involved in stroke, more than average (54.3%) of the informal caregivers had good knowledge about stroke risk factors, Sixty nine (98.6%) informal caregivers were involved in the home programme. Thirty four percent of the informal caregivers incorporated other physiotherapy programmes other than the prescribed home programme. Majority of the stroke survivors required assistance of caregivers in performing his/her home programme Informal caregivers need further assistance as adjunct for effective rehabilitation to augment hospital care for stroke survivors. The involvement of the informal caregivers must come with proper training to minimise further risk of injury.